Keep It Simple: Lowering the Barrier for Authoring Serious Games. (February 2015) - Klemke, Roland; van Rosmalen, Peter; Ternier, Stefaan; Westera, Wim
Background. Despite the continuous and abundant growth of the game market the uptake of serious games in education has been limited. Games require complex technologies and are difficult to organise and to embed in the curriculum. Aim. This article explores to what extent game templates and game authoring processes can be designed so that they can easily be adopted and adapted by teachers while only using openly available tools. Method. It discusses the design and first evaluation of two game platforms: ARGUMENT, based on a wiki, and ARLEARN, a toolkit based on openly available Google technologies. ARGUMENT is a text-based game challenging students to take a position on a given topic. ARLEARN offers an explicit mobile and virtual gameplay environment and a defined authoring process to create game scripts. Results. ARGUMENT and ARLEARN have been evaluated in four small-scale studies, where educators designed game scenarios and students played the resulting games. Conclusions. The results indicate that both tools are useful instruments that can be operated by teachers to build games and game-alike educational activities and, additionally, are a valuable step to gain experience with serious games.